A specific and bioactive polysaccharide marker for Cordyceps. (1st October 2021) - Li, Li-Feng; But, Grace Wing-Chiu; Zhang, Quan-Wei; Liu, Man; Chen, Miao-Miao; Wen, Xin; Wu, Hoi-Yan; Cheng, Hui-Yuan; Puno, Pema-Tenzin; Zhang, Ji-Xia; Fung, Hau-Yee; Bai, Su-Ping; et al.
Abstract: Cordyceps is one of the most expensive and widely used functional foods. But the authenticity is still a concern due to the lack of appropriate markers. By targeting polysaccharides, this study aimed to develop a specific, and bioactive marker for Cordyceps. Firstly, the results of screening tests of 250 samples by examining both genetic markers and polysaccharide profile showed that a unique polysaccharide fraction (named CCP) was particular to the caterpillar parts. Its potential as a marker was further demonstrated by its ability to induce NO and cytokine production in RAW 264.7 cells. CCP was characterized to be an α-1, 4-glucan with a branch at C-6 by the conventional structure analyzing and de novo oligosaccharides sequencing. The content of CCP was closely correlated to the traditional classification criteria. Generally, CCP was a marker that simultaneously enables qualitative and quantitative analysis of Cordyceps. Highlights: A unique polysaccharide fraction (named CCP) was specific to Cordyceps caterpillar. CCP, an α-1, 4-glucan, was determined by conventional and de novo oligosaccharides sequencing analysis. CCP could induce NO and cytokine production in RAW 264.7 cells. CCP was a quality marker due to the correlation of content and classification criteria.